Innovative physical impact technologies for therapeutic and preventive purposes - L. G. Agasarov; M. Yu. Yakovlev; V. A. Schernov; V. K. Frolkov (Лечащий Врач)
The article reveals personal experience of using innovative physical impact technologies and, first of all, reflexology for therapeutic and preventive purposes. A series of works carried out in several regions of the country found a significant decrease in sexual activity in more than a third of the examined conditionally healthy men. Disclosure of the mechanisms underlying the observed shifts allowed to justify and implement an effective method of spectral phototherapy - stimulation of reflex zones by light sources with spectrums emitting certain chemical elements.